Points of Light. - Villareal, Leo (ARTnews, 2009)
The article focuses on the effectiveness of the combination between light-emitting diodes (LEDs) and encode programming in orchestrating artwork. It relates to the experience of Leo Villareal, an artist who utilizes potential of computer-driven light as an artistic medium. Meanwhile, Villareal also explains how the trajectories work, which will be included in his last show at Gering & L ôpez Gallery in New York City, as well as his upcoming exhibitions early in 2010 in the U.S.